الآثار النفسية للعقم لدى عينة من النساء المترددات على مركز علاج العقم بمدينة سبها - الرشيدد. سليمة محمد على (Aljameai)
الملخص: يهدف البحث الحالي التعرف على الآثار النفسية للعقم لدى عينة من النساء المترددات على مركز علاج العقم بمدينة سبها، واشتمل البحث على عينة قوامه (70) امرأة من اللاتي يترددن على مركز علاج العقم في مدينة سبها، واتبعت الباحثة المنهج الوصفي التحليلي، واستخدمت مقياس الآثار النفسية من إعداد محمد إبراهيم عسلية (2006) وتوصلت نتائج البحث إلى: توجد فروق دالة إحصائياً على مستوى الآثار النفسية ناتجة عن العقم لدى النساء العقيمات بمدينة سبها،على الترتيب القلق أكثر تأثيرا ، ويليه الاكتئاب، من ثم الخجل، توجد فروق دالة إحصائياً على مستوى الآثار النفسية الناتجة عن العقم لدى النساء العقيمات تعزى لمتغير (من داخل العائلة- من خارج العائلة) لصالح متغير من خارج العائلة، توجد فروق دالة إحصائياً على مستوى الآثار النفسية الناتجة عن العقم لدى النساء العقيمات تعزى لمتغير عدد سنوات الزواج لصالح الفئة العمرية (40- 47) سنة، توجد فروق دالة إحصائياً على مستوى الآثار النفسية الناتجة عن العقم لدى النساء العقيمات تعزى لمتغير مستوى التعليمي دراسات عليا، لا توجد فروق دالة إحصائياً على مستوى الآثار النفسية الناتجة عن العقم لدى النساء العقيمات تعزى لمتغير مستوى الدخل. الكلمات المفتاحية: الآثار- النفسية-العقم- النساء-المترددات- مركز –علاج Abstract: The current research aims to identify the psychological effects of infertility on a sample of women attending the infertility treatment center in Sebha city, and the research included a sample consisting of (70) women who frequent the infertility treatment center in Sebha, and the researcher followed the descriptive analytical approach, and used the psychological effects scale from Prepared by Muhammad Ibrahim Asaliya in (2006) and the results of the research concluded: “There are statistically significant differences at the level of psychological effects resulting from infertility in sterile women in Sebha city, respectively, anxiety is more influential, followed by depression, and then shyness. There are statistically significant differences at the level of the resulting psychological effects. Regarding infertility in sterile women due to a variable (from within the family - from outside the family) in favor of a variable outside the family, there are statistically significant differences on the level of psychological effects resulting from infertility in sterile women due to the variable of the number of years of marriage in favor of the age group (40-47) years There are statistically significant differences at the level of psychological effects resulting from infertility in infertile women due to the variable of educational level in postgraduate studies, there are no statistically significant differences at the level of psychological effects resulting from infertility in women - Aqimat attributed to variable income level. Key words: effects - psychological - sterility - women - reluctant - center - treatment -